Pengaruh Media Edugame Berbasis Android Terhadap Kemampuan Komunikasi Matematis Siswa Pada Materi Keliling Bangun Datar Kelas IV SD Pembangunan Kota Padang - Rahmadhani, Siti; Masniladevi, Masniladevi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2017)
The purpose of this study was to determine the effect of media usage edugame android based on the ability of students' mathematical communication. This study is a quasi-experimental study, using only non-equevalent posttest control group design. The study population was all students fourth grade development of the city of Padang. The sampling technique purposive sampling technique. Selected samples of two classes, each of which will be used as an experimental class and control class. Compared learning is learning by using media edugame Scientific approach based on android with learning using a scientific approach, but only with the media in the student book. The data collection technique is to test instruments. The instrument used was a test of mathematical communication in the learning material around the Flat. Data were analyzed using t-test. RESULTS t count = 3.24 and t table = 1.67. So that t count > t table, H0 is rejected and Ha accepted. The conclusion of this study is the use of Android-based media edugame generate mathematical communication skills are better than just learning to use media in students' books.Keywords: Media edugame; Mathematical Communications; Android